Evaluation and Error Correction of Satellite Rainfall Using Dense Network of Rain Gauges Over Mumbai - Neha Rajput; Amarjyothi Kasimahanthi; Venkatrami Reddy; Hashmi Fatima; Preveen Kumar Devarajan; V. S. Prasad (Journal of the Indian Society of Remote Sensing, 2026)

Evaluation of soil moisture forecasts for landslide-prone areas in the Western Himalayas: A case study - Hashmi Fatima; M. N. Raghavendra Sreevathsa; John P. George; V. S. Prasad (Theoretical and Applied Climatology, 2026)

Understanding the role of Hedgehog signaling pathway and gut dysbiosis in fueling liver cancer - Naz Fatima; Hooriya Fatima; Sadia Ahmad; Muhammad Abu Talha Safdar Hashmi; Nadeem Sheikh (Molecular Biology Reports, 2025)

Calorimetric determination of emissivity for metallic foils: An innovative approach for thermal analysis - Abdul Rehman Hashmi; Yunfei Gao; Jiahao Yu; Haoren Wang; Bo Wang; Fatima Saadat; Zhihua Gan (International Journal of Refrigeration, 2025)

Experimental and theoretical study on the optimal placement of reflective shield in multilayer insulation systems - Abdul Rehman Hashmi; Haoren Wang; Ruyi Ji; Bo Wang; Anas A. Rahman; Fatima Saadat; Yunfei Gao; Zhihua Gan (International Journal of Refrigeration, 2025)

Monitoring of bacterial and potentially toxic elements contamination in the Rawal Lake tributaries and filtration plant - Ghazi Akbar; Joanna Kimberley Summers; Imran Hashmi; Christopher Quince; Elizabeth Wellington; Ahmed Waleed; Ebadat Ur Rehman; Namra Tariq; Zaib Un Nisa; Anam Fatima; Huma Zaheer; Sahaab Farooq; et al. (Environmental Monitoring and Assessment, 2025)

Experimental investigation of two-bed adsorption desalination cum cooling system with mass and heat recovery - Fatima Saadat; Abdul Rehman Hashmi; Shenghan Jin; Jianlin Zhu; Quanwen Pan; Zhihua Gan; Zhenyuan Xu (International Journal of Refrigeration, 2025)

Further evidence of biallelic NAV3 variants associated with recessive neurodevelopmental disorder with dysmorphism, developmental delay, intellectual disability, and behavioral abnormalities - Naseebullah Kakar; Selinda Mascarenhas; Asmat Ali; Azmatullah; Syed M. Ijlal Haider; Vaishnavi Ashok Badiger; Mobina Shadman Ghofrani; Nathalie Kruse; Sohana Nadeem Hashmi; Jelena Pozojevic; Saranya Balachandran; Mathias Toft; et al. (Human Genetics, 2025)
Neuron navigators (NAVs) are cytoskeleton-associated proteins well known for their role in axonal guidance, neuronal migration, and neurite growth necessary for neurodevelopment. Neuron navigator 3 (NAV3) is one of the three NAV proteins highly expressed in the embryonic and adult brain. However, the role of the NAV3 gene in human disease is not well-studied. Recently, five bi-allelic and three mono-allelic variants in NAV3 were reported in 12 individuals from eight unrelated families with neurodevelopmental disorder (NDD). Here, we report five patients from three unrelated consanguineous families segregating autosomal recessive NDD. Patients have symptoms of dysmorphism, intellectual disability, developmental delay, and behavioral abnormalities. Exome sequencing (ES) was performed on two affected individuals from one large family, and one affected individual from each of the other two families. ES revealed two homozygous nonsense c.6325C > T; p.(Gln2109Ter) and c.6577C > T; p.(Arg2193Ter) and a homozygous splice site (c.243 + 1G > T) variants in the NAV3 (NM_001024383.2). Analysis of single-cell sequencing datasets from embryonic and young adult human brains revealed that NAV3 is highly expressed in the excitatory neurons, inhibitory neurons, and microglia, consistent with its role in neurodevelopment. In conclusion, in this study, we further validate biallelic protein truncating variants in NAV3 as a cause of NDD, expanding the spectrum of pathogenic variants in this newly discovered NDD gene.

Spatio-temporal trends and climatology of atmospheric chlorinated hydrocarbons over Pakistan - Ahmad Hasnain; Yong Zha; Muhammad Zaffar Hashmi; Fatima Rahim; Yufeng He; Yehua Sheng (Arabian Journal of Geosciences, 2021)

Seasonal Verification of Dust Forecast over the Indian Region - Hashmi Fatima; John P. George; E. N. Rajagopal; Swati Basu (Pure and Applied Geophysics, 2017)

Examination of CK2α and NF-κB p65 expression in human benign prostatic hyperplasia and prostate cancer tissues - Fatima Qaiser; Janeen H. Trembley; Sarah Sadiq; Iqbal Muhammad; Rubina Younis; Shoaib Naiyar Hashmi; Badar Murtaza; Thomas S. Rector; Abdul Khaliq Naveed; Khalil Ahmed (Molecular and Cellular Biochemistry, 2016)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

Evaluation of short-period rainfall estimates from Kalpana-1 satellite using MET software - SOMA SEN ROY; SUBHENDU BRATA SAHA; HASHMI FATIMA; S K ROY BHOWMIK; P K KUNDU (Journal of Earth System Science, 2012)

On radiative forcing of sulphate aerosol produced from ion-promoted nucleation mechanisms in an atmospheric global model - Hashmi Fatima; H. C. Upadhyaya; S. N. Tripathi; O. P. Sharma; Fangqun Yu (Meteorology and Atmospheric Physics, 2011)